Hydrogen production from catalytic formic acid ecomposition over Zn based catalysts under room temperature - Masitah Abdul Halim Azizi; Wan Nor Roslam Wan Isahak; Norliza Dzakaria; Mohd Ambar Yarmo (Penerbit Universiti Kebangsaan Malaysia, 2019)
The depletion of petroleum sources and global warming issues has increased awareness among scientists to produce alternative energy other than the one that we always depend on, which is petroleum. Hydrogen (H2) energy is one of the alternatives that was promising as an efficient and green fuel. Meanwhile, formic acid has been detected as one of the convenient H2 source/storage material. Here, we introduce two heterogeneous catalysts for H2 generation from formic acid. Fe0.1 Zn0.9 and Fe0.5 Zn0.5 were synthesized by a modified microwave method. In this study, we report the result of a detailed study undertaken to investigate the decomposition of formic acid to H2 and carbon dioxide (CO2) using gas chromatography with thermal conductivity detector (GC-TCD). The catalyst used to decompose the formic acid was characterized by x-ray diffraction (XRD) to determine their physicochemical properties. Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) were also used to determine the surface morphology and the structure of the synthesized catalysts. The result suggested that in the dehydrogenation reaction, 90-96% of H2 was selectively produced from the formic acid with the presence of FeZn catalyst. For Fe0.1Zn0.9 catalyst, FESEM micrograph shows the particle was well dispersed, existing both away from and close proximity to 50-70 nm in size. Both heterogeneous catalysts are able to produce H2 from formic acid at room temperatures (30°C) with no additives added and with high selectivity.